Historiography and the popular fronts in France and Spain: A comparative survey - Ledesma, José Luis (Historia y Política, 2019)
This article carries out a historiographical comparison of the academic literature dealing with the Popular Front periods of France and Spain. More specifically, this text aims exploring bibliographic production on the French Popular Front from the eyes of the Spanish case in search of comparative elements in order to contemplate the research generated by the latter with a greater perspective. The important role of the Popular Front in recent contemporary Spanish historiography and the debates and controversies that its study generates justify this research. The objective is not only to pay attention to the similarities and differences in the way in which the two episodes have been historically studied. This article also addresses how the study and historiographical representation of both periods have been conditioned by their different duration and nature, the approaches used while analyzing them, the evolution and rhythms with which French and Spanish societies have approached their two popular fronts, and the role they play in the polemics and “wars of memory” in both countries.
Keywords: Popular fronts; historiography; comparative historiography; France; Spain; anti-fascism